(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
The history of such a linguistic and general cultural phenomenon as anthroponyms goes back to ancient times. Although this phenomenon has been studied scientifically for many years, a number of problems associated with it represent unexplored scientific territory. It is known that anthroponyms are usually divided into several categories, the study of each of which requires a special approach and sometimes separate methods